Pengaruh Online Travel Agent terhadap Pemesanan Kamar di Mercure Nexa Bandung - Sabar Sitompul; Nurbaeti Nurbaeti (Syntax Literate, 2023)
Technology information development changed the customer behaviour in desire in booking hotel room. Online Travel Agent is one of the most advanced products that is currently booming and change the room reservation pattern from direct reservation or go show to room reservation by Online Travel Agent. The purpose of this study was to find the information why the booking pattern changed from direct reservation to online travel agent in order to improve the e-commerce in maintain the guest to still choosing Mercure Nexa Bandung as their preferred hotel to stay in Bandung. The result of the study shows Online Travel Agent can increase hotel occupancy rate because they are accessible, efficient and effective at competitive prices as well the hotel costs with sales cost, fees and employee payroll expenses. Hotel’s management support in developing OTA is needed as an effort to increase number of room reservation from OTA.